A fresh look at strategic alliances: research issues and future directions. (10th March 2009) - Culpan, Refik
This article reviews the current state of strategic alliances between and among firms by discussing the confusion concerning their epistemology and taxonomy; it offers a plain definition and typology of such ventures. Also examined are their evolution and theoretical foundations and important research questions reflected in the extant literature. After clarifying existing misconceptions and presenting a systematic treatment of strategic alliances, it aims at delineating new research issues and stimulating further research for advancement of the current body of knowledge on interfirm cooperation.